O processo de integração social da criança e adolescente imigrante na escola pública - Fabiano, Maria Lucia Alves (2020)
The object of this study is the immigrant child and/or adolescent within the school environment. The problem of the research is to verify what factors interfere in the relationship of the immigrant child and/or adolescent with the public school and, to what extent, the school environment favors their insertion, adaptation and integration, seeking to understand this process through the perception that the immigrant students have of the school and the factors that influence their adaptation and development. The pedagogical responses that the school implements to welcome the immigrant community were also approached. Thus, the objectives were to characterize how intercultural communication between the school and the foreign student is processed and to identify what approaches and projects are being used to favor this integration to a new territory, culture and language. The research was conducted in a public school located in the central region of the city of São Paulo, which serves a territory with a large presence of immigrants, such as Bolivians, Paraguayans, Peruvians, Chinese, among others¸ where lower income social class people predominate, people considered in need, when we refer to precarious housing and also to the exhausting workload to which immigrants located in the region are subjected to. Initially, the document presents an overview of contemporary migratory flows, followed by a reflection on the issue of territory and territorialities for the immigrant and how school fits into this process. It also discusses how the Brazilian public school of the 21st century recognizes the interculturality and diversity in its learning process, as well as the presence of immigrant students, and the challenges and obstacles they face in the school environment. The study allowed us to realize that, although initially troubled, mainly due to the lack of mastery of the Portuguese language, the process of integration and learning of the immigrant children and/or adolescent, over the years, have been proved satisfactory. The challenge perceived by the study is the lack of a broader inclusion project that addresses the presence of the immigrant student in the classroom, as well as the problems surrounding the community that his/her family chose to establish a new territory. Such a study would ensure the integration and would minimize discrimination and prejudice, still very present in Brazilian society and, consequently, within the school itself